Design of novel metal chalcogenide photoanodes supported with reduced graphene oxide for improvement of photoelectrochemical hydrogen evolution - Neli, Ozlem Uguz; Budak, Ozlem; Karaca, Fatma; Keskin, Bahadir; Ozkaya, Ali Riza; Koca, Atif (ELSEVIER SCIENCE SA, 2023)
Designing new photoanodes with high efficiency provides an effective route to develop photoelectrochemical hydrogen production. In this work, quaternary metal chalcogenides (CdZnMSSe (M: Ni, Cu, Mo)) and reduced graphene oxide-quaternary metal chalcogenide (RGO-CdZnMSSe) composite films are fabricated by simple one-step electrodeposition process. The photoanodes formed of quaternary metal chalcogenides and the incorpora-tion of RGO in these composite films increase charge transfer capability and separation ability compared to cadmium-based photoanodes, leading to enhancement of the photoelectrochemical hydrogen production activ-ity. A superior photocurrent response is recorded for RGO(0.25)-Cd0.8Zn0.2Ni0.2S0.2Se0.8 (5.34 mA cm-2 at 0.8 V vs RHE). In addition, the maximum ABPE value of RGO(0.25)-Cd0.8Zn0.2Ni0.2S0.2Se0.8 is determined as 1.95%. The achieved results offer a new insight into highly efficient next generation-photoanodes to convert solar energy to hydrogen.
Keywords: Electrodeposition; Quaternary metal chalcogenide thin films; Reduced graphene oxide; Photoelectrochemical performance; PHOTOCATALYTIC ACTIVITY; WATER; NICKEL; PERFORMANCE; EXCITATION; MECHANISM; EFFICIENT; NANORODS; FILMS; CDSE; Chemistry